Numerical Prediction of Cantilevered Reinforced Concrete Wall Subjected to Blast Load - Nasly, Mohamed Ali; Sharifah Maszura, Syed Mohsin; Mazlan, Abu Seman; Zainorizuan, Mohd Jaini (Universiti Teknologi Malaysia, 2015)
Aggressor attack using improvised explosive not the only source for blast load. Some commercial equipment and daily activities can contribute as well, such as electrical transformers, gas pipelines and industrial plants. Normally, reinforced concrete wall is used as the protection. Therefore, it is vital to estimate the structure damage. In this paper, the behaviour of cantilevered reinforced concrete (RC) wall subjected to blast load is investigated through numerical simulation. A three-dimensional solid model, including explosive, air and RC wall is simulated. The wall has a cross-sectional dimension of 1829 mm  1219 mm with wall thickness of 152 mm and 305 mm thickness of strip footing. It is subjected to 13.61 kg Trinitrotoluene (TNT) explosive at 1.21 m standoff distance from the centre. Concrete and steel material model behaviour considers the high strain rate effect and dynamic loading. The Arbitrary Langrange Euler (ALE) coupling interface between air and solid are applied to simulate the damage mechanism of RC wall. A Comparison between experimental data on blast pressure and damage pattern shows a favourable agreement. The numerical result shows, the displacement-time history on each side is in a contrary direction. A permanent deformation is occurred and, the blast pressure near to the wall base is the highest.